Cationic and anionic environments in LiTFSI-doped di-ureasils with application in solid sate electrochromic devices - Nunes, Sílvia (2008)
FTIR and Raman spectroscopies were used to investigate the cation/polymer, cation/urea bridge, cation/anion and hydrogen bonding interactions in poly(ethylene oxide)/siloxane di-ureasil networks prepared by the sol-gel route and doped with LiTFSI. Materials with compositions 200>n>5 (where n expresses the molar ratio of OCH2CH2/Li+) were studied.